Behavior Analysis and Socio-education: Contributions to work with adolescents in conflict with the law - Luiz, Fernanda Bordignon; Parapinski, Renata Teixeira (Perspectivas em Análise do Comportamento, 2022)
Despite important social advances in Brazil in terms of legislation and public policies relating to the young population, children and adolescents are still deprived of basic rights. Thus, involvement with crime becomes an alternative, further increasing the situation of vulnerability. Adolescents in conflict with the law are given socio-educational measures in order to promote resocialization and guarantee their rights. The aim of this study is to chacacterize the possibilites of Psychology work tirh adolescentes in conflict with the law, based on concepts and guiding principles of Behavior Analysis. Some concepts can guide professional practice, including the differentiation between complaints and social needs, in which relevant behaviors to be developed in the population are identified. In addition, the notion of behavior, which involves differentiating the individual’s interaction from the organism’s response. Another concept is the distinction between objective-behavior proposition, which guides the intervention, and activities that are a means to develop such objective. Clarity about the principles of BA for professional practice contributes to interventions with adolescents to develop relevant behaviors and help them to interact in a more beneficial way with the environment.